Addressing Student Needs Throughout Development - Couture, Shari (Canadian Journal of Counselling and Psychotherapy, 2007)
This study surveyed 651 adolescents in grades 7, 8, 9, 10, 11, and 12 to explore differences in their self-perceived needs. Students in junior high grades reported higher needs in the areas of setting clear and consistent expectations, academic skills, sexuality, physical well-being, and self-esteem, while senior high grades highlighted future oriented needs concerning careers, academics and self-management. Grade 7 students placed more emphasis on interpersonal relationships, involvement with other students, and home life than did other junior high students. No differences were found between the senior high grades. Gender differences also were found across grades. The results highlight the importance of considering developmental differences when planning programs to address the needs of adolescent students.